Photon efficacy and cost investigation of LEDs at different wavelengths and color temperatures for horticulture - Ten It Wong; Xiaodong Zhou (Discover Agriculture)
Abstract Photon efficacy (PE) is defined as the photon numbers generated by 1 joule (J) of power consumption, which is a key indicator on energy efficiency of LED lighting. PE calculated by LED datasheet includes photons irradiating in all directions, therefore deviates far from the actual PE of LED grow lights in indoor farms where only photons shining on plants are counted. To measure the PEs of different types of LEDs for plant growth accurately, we designed and fabricated LED panels for 16 types of LEDs at different wavelengths and color temperatures under plant growth conditions. We characterized the LED panels by an optical spectroscopy setup, in which an optical fiber probe mapped the optical spectra of LEDs on the plant growth area to detect the photon numbers reachable to plants. We found that at plant growth conditions, the LED panels at 660, 730 and 450 nm have higher PEs of 3.84, 3.39 and 2.38 µmol/J, respectively, followed by 2.31, 2.08 and 2.03 µmol/J for white LEDs at the color temperatures of 5700 K, 5000 K and 4000 K, respectively. We further compared the LED costs and concluded that 4000 K, 3000 K, 475 nm and 5700 K LED panels are most cost-effective to build at an LED cost of 0.15 $$-$$ - 0.21 US$ per µmol/s. Our findings provide a good reference for plant scientists and horticulture practitioners to understand LED lighting cost at different wavelengths and color temperatures for plant growth, for them to develop the lighting recipes effectively and estimate farm operating cost more precisely.